African Governance Report III - 2013 - Nations Unies (United Nations, 2013)
This report is the most comprehensive report on governance in Africa, assesses and monitors the progress African countries are making on governance, identifies capacity gaps in governance institutions and proposes polices and strategic interventions aimed at promoting good governance on the continent. It focuses on political and economic governance, development of the private sector and corporate governance, checks and balances in political power, institutional effectiveness and accountability of the executive, human rights and the rule of law, corruption and institutional capacity building. The theme of this third edition of the report revolves around elections in Africa becoming a significant tool for political change and genuine democratization.